Studi penambahan chemical pada produk migas guna mengurangi dampak negatif terhadap lingkungan proses distribusi - Saputra, Ahmad Rialdi Rangga; Safitri, Ardini Nadia; Setiawan, Hanif Ash Shiddiq; Karina, Reva; Venriza, Oksil (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The distribution of fuel impacts the environment through emissions and combustion residues. This study evaluates hydrocarbon compounds in petroleum products with ethanol addition to enhance octane ratings and reduce emissions. Gravimetric methods assessed ash content, FTIR analyzed organic compound absorption via functional groups, and UV-Vis spectrophotometry measured toluene levels through absorbance. Results showed ethanol blending with biodiesel reduced ash content from 74.48 mg/L to 64.99 mg/L, a 9.4% decrease, indicating a positive environmental impact. UV-Vis analysis revealed increased toluene content, reflecting higher octane value and potential emission reductions. Additionally, blending Pertamax with ethanol showed increased oxygenated compounds, such as alcohols and esters, at a 1600 nm wavelength. In conclusion, adding ethanol positively affects the environment by reducing emissions and improving octane ratings. However, further analysis is needed to comprehensively assess its environmental impact.